The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/ijms24065612
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Germline and Somatic Alterations in Human MRE11, RAD50, and NBN Genes Coding for MRN Complex

Abstract: The MRE11, RAD50, and NBN genes encode for the nuclear MRN protein complex, which senses the DNA double strand breaks and initiates the DNA repair. The MRN complex also participates in the activation of ATM kinase, which coordinates DNA repair with the p53-dependent cell cycle checkpoint arrest. Carriers of homozygous germline pathogenic variants in the MRN complex genes or compound heterozygotes develop phenotypically distinct rare autosomal recessive syndromes characterized by chromosomal instability and neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 144 publications
0
7
0
Order By: Relevance
“…This study confirmed the well-known fact that mutations in Mre11 are associated with the reduction or loss of other proteins of the MRN complex, which makes the specific role of Mre11 in cancer predisposition even more elusive [ 75 ]. However, the occurrence of germline Mre11 alterations in a minority of breast cancer patients observed in these studies has not been confirmed in ample case population studies [ 70 ]. It has also been suggested that mutations in Mre11 are associated with increased susceptibility to colorectal cancer.…”
Section: Review and Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…This study confirmed the well-known fact that mutations in Mre11 are associated with the reduction or loss of other proteins of the MRN complex, which makes the specific role of Mre11 in cancer predisposition even more elusive [ 75 ]. However, the occurrence of germline Mre11 alterations in a minority of breast cancer patients observed in these studies has not been confirmed in ample case population studies [ 70 ]. It has also been suggested that mutations in Mre11 are associated with increased susceptibility to colorectal cancer.…”
Section: Review and Hypothesismentioning
confidence: 99%
“…Similar to AT, cells derived from patients with NBS exhibit accelerated shortening of telomeres, loss of intra-S and G2/M checkpoint control, and genomic instability [ 69 ]. Another study including 241 cases reported a median age of cancer onset of 9.1 years with a probability of 20-year survival of 44.6% [ 70 ], whereas a murine model in which exons 4 and 5 were replaced by neo did not show increased tumor incidence [ 71 ]. Dumon-Jones et al generated heterozygous knockout (Nbn +/− ) mice that developed a wide array of tumors in addition to lymphomas and gamma-radiation-enhanced tumor development [ 72 ].…”
Section: Review and Hypothesismentioning
confidence: 99%
“…Once a DSB occurs, MRN complex recognizes damaged DNA and initiates a signaling cascade to activate cellular response to repair the break [ 38 ]. MRN complex facilitates autophosphorylation of ataxia telangiectasia mutated (ATM) at serine 1981 (S1981) and autoacetylation of ATM at lysine 3106 (K3106) [ 39 , 40 ].…”
Section: Phase Separation In Dna Double-strand Break Responsementioning
confidence: 99%
“…Specifically, Otahalova et al [ 7 ] outline the structural characteristics of the MRE11, RAD50, and NBN proteins and the assembly and functions of the MRN complex from the perspective of clinical interpretation of germline and somatic alterations in the MRE11, RAD50, and NBN genes. They describe the structure of the MRN Complex and its function in double-strand break (DSB) repair and analyze the different germline alterations of the MRN complex genes in autosomal recessive syndromes, as well as the association between heterozygous germline alterations in these genes and cancer predisposition.…”
mentioning
confidence: 99%
“…They describe the structure of the MRN Complex and its function in double-strand break (DSB) repair and analyze the different germline alterations of the MRN complex genes in autosomal recessive syndromes, as well as the association between heterozygous germline alterations in these genes and cancer predisposition. Their review finally explores the role of somatic alterations in the MRN complex genes in different tumors [ 7 ].…”
mentioning
confidence: 99%